MEDIEVAL LITURGY AND LUTHER’S ATTEMPT AT ITS REFORM IN THE 16TH CENTURY. - Valčová, Katarína (Sincronía, 2025)
This article examines the development of medieval Christian liturgy and Martin Luther’s attempt at its reform in the sixteenth century, aiming to analyze the tensions between official liturgy, personal piety, and the proclamation of the Gospel. The central argument holds that medieval liturgy gradually fostered a separation between clergy and laity, resulting from increasing ritual complexity, the exclusive use of Latin, and the rise of private devotional practices that limited communal participation. Methodologically, the study adopts a historical-theological approach based on the analysis of medieval liturgical sources, patristic writings, and Luther’s key texts, particularly Formula Missae (1523) and Deutsche Messe (1526). The article shows that Luther valued the inherited liturgical tradition but sought to reform it according to the principle of the primacy of the Gospel, rejecting the sacrificial understanding of the Mass and emphasizing the need for a clear and intelligible proclamation of the Word. Key elements of Luther’s reform are examined, including the use of the vernacular language, the centrality of the sermon, active congregational participation through singing, and Christian freedom regarding ritual forms. The scope of the study lies in demonstrating that Luther did not aim to abolish the Mass but to theologically reorient it so that liturgy might function as a living space for the communication of the Gospel and the formation of communal faith.